HE FEATURES OF STUDY OF SUBJECT "SAFETY OF VITAL FUNCTIONS" AT IVANO-FRANKIVS’K NATIONAL TECHNICAL UNIVERSITY OF OIL AND GAS - Лялюк-Вітер, Г. Д.; Семчук, Я. М.; Стеліга, І. І.; Савчук, Л. Я.; Чичул, Х.-М. М. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Pulse, 2019)
The process of teaching "Safety of vital functions" at Ivano-Frankivsk National Technical University of Oil and Gas. It is one module subject. Two meaning modules are described and nine themes practical classes are given. Mark system of student’s knowledge are presented.